2006
DOI: 10.1592/phco.26.6.806
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Rasburicase 6 mg in the Management of Tumor Lysis Syndrome in Adults

Abstract: Rasburicase is currently approved at a dosage of 0.15-0.2 mg/kg once/day for 5 days in pediatric patients with cancer to lower plasma uric acid concentrations and manage tumor lysis syndrome (TLS). Information on rasburicase dosing in adults is limited, with some data on using rasburicase as a single dose instead of multiple daily doses. Therefore, we evaluated the efficacy of a single dose of rasburicase for preventing or managing TLS in adults. We collected retrospective data for 11 adults with hematologic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 8 publications
3
56
0
Order By: Relevance
“…In these 10 patients, uric acid concentrations remained low despite subsequent chemotherapy and none required additional rasburicase doses. 11 A similar efficacy of single dose rasburicase was also observed in our case series with patients who were predominantly Chinese. Several small-scale studies [4][5][6][7][8] have also shown that a single dose of rasburicase produces a rapid uric acidlowering effect that is beneficial for patients manifesting TLS.…”
Section: Discussionsupporting
confidence: 86%
“…In these 10 patients, uric acid concentrations remained low despite subsequent chemotherapy and none required additional rasburicase doses. 11 A similar efficacy of single dose rasburicase was also observed in our case series with patients who were predominantly Chinese. Several small-scale studies [4][5][6][7][8] have also shown that a single dose of rasburicase produces a rapid uric acidlowering effect that is beneficial for patients manifesting TLS.…”
Section: Discussionsupporting
confidence: 86%
“…It is logical to block xanthine oxidase, which converts purine metabolites such as hypoxanthine and xanthine to UA, thereby reducing the production of UA (2,3,8). However, xanthine oxidase inhibitors do not reduce the already generated UA.…”
Section: Discussionmentioning
confidence: 99%
“…Allantoin is readily excreted by the kidneys. The UA-lowering efficacy of rasburicase is prompt and potent, and the administration of rasburicase appears to be extremely well tolerated (6)(7)(8)(9)(10). The approved method of administration in Japan is 0.2 mg/kg once daily, as an intravenous infusion administered over a 30-min period, for a maximum of seven days (11).…”
Section: Introductionmentioning
confidence: 99%
“…An expert panel convened in 2010, sponsored by the manufacturer of rasburicase (SanofiAventis), recommended the prophylactic use of rasburicase in adults with a high-risk malignancy, with other patients receiving rasburicase after chemotherapy in the setting of elevated uric acid levels (51). Several cohort studies have demonstrated persistently suppressed serum uric acid concentrations with one-time dosing; a dose of 0.15 mg/kg seems to be a clinically reasonable and cost-effective approach (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). Repeat dosing may be needed if uric acid remains at or increases above 8.0 mg/dl after the initial dose (75).…”
Section: Recombinant Urate Oxidasementioning
confidence: 99%